Participação das citocinas IL-4, IL-13 e IL-33 na resposta imunológica induzida pela infecção experimental por Strongyloides venezuelensis emcamundongos - Adriana Fernandes Silva (2012)
Even though the importance of Th2 response in protection against nematodes is well established, the effector mechanism controlling the parasite can be different in each species. It was demonstrated in mice infected with Strongyloides venezuelensis the importance of IL-4R/Stat 6 activation in the induction of a protective response, however the involvement of IL-4, IL-13 and IL- 33 in this mechanism has not yet been established, being the main focus of this work. For this purpose, we used mice deficient in the production of IL-4 (IL-4-/ -) primarily infected or re-infected with S. venezuelensis. After infection, IL-4-/ - and wild type mice were treated with neutralizing antibody against IL-13 or exogenous IL-33. Comparing to wildtype mice, IL-4 deficient mice showed a significant increase in parasite burden and a delay in parasite elimination without changes in the fecundity. During primary infection, the IL-4 deficiency resulted in a smaller proportion of CD4+ cells in the mesenteric lymph nodes and decreased the production of IL-10, IL-5 and IFN- at the site of the lamina propria. Furthermore, the absence of IL-4 prevented IgE production, and reduced EPO and MPO levels in the host intestine. In re-infected animals, the deficiency of IL-4 resulted in an increase in the proportion of CD4+ cells in mesenteric lymph nodes and also in the intracellular detection of IL-10 in CD4+ cells in the intestinal mucosa. Along with this, the IL-4 deficiency resulted in ablation of IgE production, in a lower production of IgG1 and in a reduced degranulation of neutrophils in the intestine. The neutralization of IL-13 did not affect S. venezuelensis parasite burden but decreased the fecundity of the parasites and resulted in a lower production of parasite-specific IgM in IL-4-/- mice and an increase in eosinophil peroxidase during the infection. IL-33 administration did not affect the worm burden and fecundity but increased the IgE production by IL-4-/- mice. The results indicate that the control of S. venezuelensis infection is dependent on mechanisms mediated by IL-4 and not by IL-13 or IL-33. Moreover, the data suggests that IL-13 participates in antifecundity mechanisms during S. venezuelensis infection.